Effect of compressibility on heat transport phenomena in aerogel-treated nonwoven fabrics. Issue 9 (1st September 2016) - Venkataraman, Mohanapriya; Mishra, Rajesh; Kotresh, T.M.; Sakoi, Tomonori; Militky, Jiri
Abstract : The heat transport properties observed in nanostructured materials such as aerogel-treated nonwoven fabrics are promoting revolutionary breakthroughs as thermal insulators. This article is focused on the thermal transport characteristics of nonwoven fabrics treated with aerogel for potential uses in thermal protective applications. Highly efficient aerogel thermal blankets are now considered a viable option in applications such as clothing, building, and pipelines. A variety of fiber and fabric structures or finishing parameters influence the functional properties of nonwoven materials. In order to assess the thermal properties of aerogel-treated nonwoven fabrics, the KES Thermolabo II and NT-H1 (plate/fabric/plate method for thermal conductivity, q max cool/warm feeling, and thermal insulation) was used. Fabrics of higher thicknesses show lower heat conductance and therefore higher thermal insulation properties. It has been found that thermal insulation is also related to the weight and compressional properties of the fabric. To make an insulating material effective, it should have low compression set and high resiliency to make the still air to be entrapped into the fibrous material.